PENERAPAN METODE BERNYANYI DALAM MENINGKATKAN PENGUASAAN MUFRODAT DALAM PEMBELAJARAN BAHASA ARAB DI MTS AL-JAM'IYATUL WASHLIYAH TEMBUNG - Mita Atiiqah Br Ginting; Nina Wandana; Siti Rahma (Yayasan Haiah Nusratul Islam, 2023)
Method is a method used by an educator in applying learning in the classroom. The learning will be up to or accepted by the student/i if using appropriate methods. There are many learning methods used by educators, one of which is the singing method. Mts Al-Jam’iyatul Washliyah Tembung applies the method of learning Arabic with a singing method. This study uses qualitative methods and the results obtained are the results of observations made by researchers. The singing method is able to foster the spirit of students/i Mts Al-Jam’iyatul Washliyah Tembung in following learning. The method used is also effective which makes the student/i understand the learning material.